Prescribing antipsychotics in older people: A mini-review. (October 2018) - Behrman, Sophie; Burgess, Jennifer; Topiwala, Anya
Highlights: Evidence for efficacy of antipsychotics for many conditions in the elderly is weak and extrapolated from younger adults. Risperidone, olanzapine, and aripiprazole appear to be the most effective antipsychotics in treating behavioural symptoms in dementia. Antipsychotic use in elderly is associated with serious side-effects. Careful consideration of comorbidity and polypharmacy is imperative. Abstract: Antipsychotic medications are widely prescribed in elderly populations for a range of psychiatric symptoms. Evidence for their efficacy in this population is limited, and such individuals are at increased risk of numerous side-effects, including stroke and death, particularly in those with dementia. There appears to be a mismatch between the current evidence base and what is occurring in clinical practice, especially in the use of antipsychotics to treat delirium and behavioural and psychological disturbance in dementia. We advise caution in the prescription of antipsychotics in older people and seeking specialist advice.